2013
DOI: 10.5053/ejobios.2013.7.0.5
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal stickiness and related meiotic irregularities in Inula racemosa - a critically endangered medicinal herb of North Western Himalayas

Abstract: Background:The species Inula racemosa, a rare species of Kashmir Himalaya, has been included in the list of endangered species of India. In the present study, we aimed to make a more formal quantitative analysis of the fertility of I. racemosa, wild as well as transplanted populations, using a meiotic behaviour analysis and pollen viability test. Material and Methods: Inflorescences at an ideal stage for meiotic study were collected and fixed in acetic ethanol (1:3) for 24 h and stored in 70% alcohol under ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The present study on meiotic behavior revealed that there are significant meiotic irregularities that can be correlated with the low seed set. The presence of meiotic irregularities leads to pollen sterility which constraints the sexuality of the species, and thereby increases the frequency of genetically uniform individuals in the wild populations (Shabir et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The present study on meiotic behavior revealed that there are significant meiotic irregularities that can be correlated with the low seed set. The presence of meiotic irregularities leads to pollen sterility which constraints the sexuality of the species, and thereby increases the frequency of genetically uniform individuals in the wild populations (Shabir et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal stickiness can occur due to the presence of mutant genes (Kaul and Murthy 1985). Shabir et al (2013) also concluded that chromosome stickiness is genetically controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Rana et al (2013) have opined that the degree of chromatin stickiness affects the pollen fertility wholly or partially. Shabir et al (2013) suggested that as a consequence of chromatin stickiness and other meiotic abnormalities, heterogenous-sized pollen grains and low amounts of pollen sterility could be observed. Pagliarini et al (2000) observed that unviable pollen grains are produced due to intensive chromatin stickiness.…”
Section: Discussionmentioning
confidence: 99%